The last mile(s) in modern input distribution: Evidence from Northwestern Ethiopia - Minten, Bart; Koru, Bethlehem; Stifel, David (International Food Policy Research Institute, 2013)
Based on unique data from a quasi-experimental setting in northwestern Ethiopia, this study examines the “last mile(s)”—from the input distribution center to the farmer—in the chemical fertilizer and improved seed distribution system. We find that increasing transaction and transportation costs over a 35 kilometer distance, along a route mainly accessible to foot traffic only, lead to a 50 percent increase of the prices of chemical fertilizer and to a 75 percent reduction in its use.